Analisis Perbandingan Penggunaan State Management pada Aplikasi Ditonton menggunakan Framework Flutter - Muhammad Hafid Nur Azis; Aryo Pinandito; Intan Sartika Eris Maghfiroh (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2023)
Ditonton application is an application created using the Flutter framework to display a list of films that have been shown, along with ratings, genres, and synopsis for each film to help users decide which films to watch. In Ditonton application, there are several features that utilize various data processing models that use state management in the application. Researchers want to see the differences in the performance of implementing state management into applications based on three categories, namely memory usage, execution time, and CPU utilization. In testing the state management that will be tested and compared in this study is Provider and BLoC which are the most frequently used state management. The research was conducted by analyzing the implementation of state management, collecting performance test data, and comparing performance test data through 2 stages including the normality test and parametric or non-parametric statistical tests depending on the data from each category. From the results of the calculations that have been carried out, the results show that in the comparison of the use of state management in the memory usage category there is no difference from the values that have been tested. Whereas in the comparison of the use of state management in the categories of execution time and CPU utilization there are differences from the values that have been tested.